Asbestos and cancer in Latin America and the Caribbean: we may have won some battles, but definitely not the war - Abraham Hernández-Blanquisett; Angelina Álvarez-Londoño; Maria Cristina Martinez-Avila; Sofía Covo-Camacho; Valeria Quintero-Carreño (SAGE Publishing, 2021)
Only six countries have banned the industrial use of asbestos in Latin America and the Caribbean. In fact, the industrial use of asbestos appears to be growing in this region. Asbestos is one of the most dangerous natural substances in the world, it is contained in several types of rocks (such as serpentinites, mafic and ultramafic rocks) but fibers can be released to the atmosphere both by natural and antropogenic sources. Six countries have banned the industrial use of asbestos in this region, we expected that laws established before 2007 would be less adherent to the 2007 WHO/ILO recommendations. In contrast, the Chilean law of 2001 is one of those that most adheres to international recommendations along with the Colombian law of 2021. Which means that the newest laws are not necessarily the strongest. This article aims to draw a regional overview of the laws against asbestos production in Latin America and the Caribbean, highlighting the strengths and weaknesses of each national policy. We recommend that countries that have already banned asbestos consider updating and strengthening their existing laws and develop clinical guidelines for the management, monitoring, and rehabilitation of asbestos-related diseases. The challenge of asbestos goes far beyond a prohibition law.